STUDENT SELF-REGULATED LEARNING (SSRL) DALAM MATA KULIAH BAHASA INGGRIS PADA MAHASISWA TAHUN KEEMPAT JURUSAN BAHASA INGGRIS FKIP UNIVERSITAS MUHAMMADIYAH TANGERANG - Putra, Aidil Syah; Latifah, Nur (JPPGuseda | Jurnal Pendidikan & Pengajaran Guru Sekolah Dasar, 2018)
Learning English is the activity for getting the knowledge about English. English should be learned since the beginner level to the advance level. There are some characteristics of students in learning process at classroom, such as they can pay attention to the teacher, and have purpose in learn. It is called Self-Regulated Learning. The design of this research was descriptive qualitative research. The setting of this research is FKIP Universitas Muhammadiyah Tangerang. There were five classes English Language Department at Fourth Year English Language Department. From five class, there were choosing 30 students for the participant. In choosing the participants the researcher used purposive sampling. The researcher used questionnaire to collect the data, and used peer debriefing to check the trustworthiness of the data. The result showed that process of self-regulated learning that used by students were goal setting, planning, self-motivation, attention control, self-monitoring, help-seeking, and self-evaluation. The highest of total value was goal setting 440, self-monitoring with the total value 420, self-evaluation with the total value 410, self-motivation with the total value 392, help-seeking with the total value 306, planning with the total value 305, and the least is attention control with the total value 300. The highest of total value of self-regulated learning was goal setting. So, it can be concluded that the fourth year students of FKIP Universitas Muhammadiyah Tangerang had applied the process of self-regulated learning, the most implemented process was goal setting and the least process was attention control.  Keywords: Self – Regulated Learning, Learning English